(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
Intellectual property, in its broadest sense, refers to the legal rights that arise as a result of intellectual work in the disciplines of industry, science, literature, and the visual arts. There are two primary reasons why countries enact legislation to protect intellectual property. To begin, the moral and economic rights of creators in their works of art, as well as the rights of the general public in access to such works of art, must be given legal expression. Secondly, as a purposeful act of government policy, it is intended to inspire creativity, the distribution and application of its findings, and to promote fair commerce in order to contribute to economic and social progress.